Fabrication of YBa2Cu3Oy coated conductor by Vapor-Liquid-Solid growth technique using a Reel-to-Reel system. (July 2020) - Yasuda, Kento; Ito, Tomohiro; Tsuchiya, Yuji; Ichino, Yusuke; Ichinose, Ataru; Yoshida, Yutaka
Abstract: To optimize the production cost of REBCO-coated conductors, the deposition rate needs to be increased. The vapour-liquid-solid (VLS) growth technique is a suitable method for fabricating a film with a high deposition rate and good crystal orientation. This technique enables growth through a liquid phase. There have been studies conducted on the fabrication of REBCO films using the VLS growth technique. However, very few studies have been performed on a system for depositing REBCO-coated conductors with VLS growth techniques while moving the substrate. In this study, we evaluate the reel-to-reel pulsed laser deposition system, pure YBCO-coated conductors, and the BHO 3 vol% doped YBCO-coated conductors, which were fabricated using the VLS growth technique under high-speed deposition conditions with an average deposition rate of 17 nm/s, achieved J c > 2.0 MA/cm 2, J c > 1.0 MA/cm 2 at 77 K and self-field, respectively. In addition, the J c in the magnetic fields of the BaHfO3 -doped YBCO coated conductors could be improved by introducing discontinuous BHO nanorods.